WHITE BOX TESTING PADA SISTEM PEMESANAN DESAIN SABLON BERBASIS WEB - Abdi Pandu Kusuma; Bayu Setiawan (Universitas Islam Lamongan, 2018)
Ordering a screen printing design is built as a supporting tool to anticipate cheating buyers in ordering goods that are normally done through the marketplace. By using this system the user must enter the order number obtained after the customer makes an order in the marketplace for verification if they want to make a design order. Admin can manage user access to order designs and manage the design queue properly. White box testing method is done to find out how the system works structurally, besides to find out things that might happen when the system is run. In the white box test on the user login page and the design orderi ng page, the system works well as evidenced from the testing phase as in Cyclomatic Complexity and Matrix produces a value of 2 for the user login page and 1 for the design message page.